The installation of pad foundation / Muhammad Aiman Azami - Azami, Muhammad Aiman (2017)
Atira Group Development Sdn. Bhd. is the business group that manage by the Atira Group is a group of companies led business and run by Bumiputera. It is led and managed by a Board of Directors and a dynamic and experienced owner. The first company that was born in the Group is Atira Development (M) Sdn. Bhd. The first body and operates on 09/04/1994. The establishment of the first function is running the business services activities of City Planning, Project Management and Building Contractors. In line with current and business trends and events complex, the company Another company was established according to the needs and special functions to carry out certain activities so system management is easy and efficient.